Zygmunt Bauman goes to the cinema: films to understand liquid modernity (Research, Society and Development, 2020)
This paper aims to put in dialogue some cinematographic works with the main concepts of liquid modernity, a term coined by the Polish sociologist Zygmunt Bauman to characterize the current era. Coming from a dissertation that proposed to discuss, in a teachers’ training course, the didactic potential of cinema as an invitation to a better understanding of liquid modernity, this text presents a brief discussion about its conceptualization, followed by the state of knowledge constructed from researches that considered some cinematographic works as representative of liquid modernity aspects. The construction of knowledge state led to the realization that the research found dealt with more prominently subjective aspects of the construction of the postmodern individual’s identity and, only to a lesser extent, discussed the relationships between the individual and social groups or institutions. In the end, this article highlights and encourages the use of cinema for pedagogical purposes and leaves indications of other works which can increase the dialogue between Bauman’s sociology and cinematographic productions.